Citrus sinensis MYB transcription factors CsMYB330 and CsMYB308 regulate fruit juice sac lignification through fine-tuning expression of the Cs4CL1 gene. (December 2018) - Jia, Ning; Liu, Jiqin; Sun, Yufeng; Tan, Penghui; Cao, Hao; Xie, Yingying; Wen, Boting; Gu, Tianyi; Liu, Jiameng; Li, Minmin; Huang, Yatao; Lu, Jia; et al.
Highlights: We isolated two TFs and investigated their function in the juice sacs lignification. We found that two TFs can recognize and bind AC elements in the Cs4CL1 promoter. We found that two TFs finely regulate expression of the Cs4CL1 gene. The CsMYB330 was a transcriptional activator, whereas CsMYB308 was a transcriptional repressor. Abstract: Lignin is one of the most important components of the plant cell wall, and the expression and transcriptional regulation of lignin biosynthesis-related genes have been studied widely in Arabidopsis and other plants. Citrus fruit juice sacs often undergo lignification, particularly during fruit ripening and storage periods; however, the underlying genetic mechanisms have been little investigated. In this study, we isolated and identified CsMYB330 and CsMYB308 transcription factors, and found that their expression levels are significantly altered during the lignification of citrus fruit juice sacs. We found that CsMYB330 and CsMYB308 can recognize and bind AC elements in the Cs4CL1 promoter and finely regulate expression of the Cs4CL1 gene. In this regulatory process, CsMYB330 was identified as a transcriptional activator, whereas CsMYB308 appears to be a transcriptional repressor. In addition, using a transient assay, we demonstrated that expression of the Cs4CL1 gene is significantly altered in fruit juice sacs overexpressing these two transcription factors. These results indicate that the transcription factors CsMYB330 and CsMYB308 play important roles in the lignification of citrus fruit juice sacs and provide novel insights into the transcriptional regulation associated with fruit juice sac lignification.